Counselor Communication Strategy in Handling Deviant Behavior of Al-Mawaddah Students - Zakiyah Romadlany; Zyda Firizqiyati Fudyus (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study examines the communication strategies employed by counselors in addressing deviant behavior among santri at Pondok Pesantren Nurul Jadid, Al-Mawaddah area. Deviant behavior in this context is not merely a matter of discipline but is closely related to interpersonal communication dynamics within the guidance process. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation of counseling sessions, and documentation. The data were analyzed using an interactive model involving data reduction, display, and conclusion drawing. The findings indicate that effective counseling is achieved through empathetic, dialogical, and persuasive communication grounded in the principle of bil hikmah. Such strategies foster an open and supportive environment, encourage self-reflection, and enhance santri’s internal awareness to improve their behavior. This study also proposes the “CURHAT” counseling communication model as a systematic framework for guiding behavioral change. The findings highlight the importance of humanistic and participatory communication in ensuring effective counseling practices and offer practical insights for developing Islamic-based counseling approaches in educational settings.